Cerium, manganese and cerium/manganese ceramic monolithic catalysts. Study of VOCs and PM removal - Colman Lerner, Jorge Esteban (2016)
Ceramic supported cerium, manganese and cerium-manganese catalysts were prepared by direct impregnation of aqueous precursor, and characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), Brunauer-Emmett-Teller method (BET), temperature programmed reduction (H2-TPR), X-ray photoelectron spectroscopy (XPS) acidity measurements and electricalconductivity. The catalytic activity was evaluated for VOC (ethanol, methyl ethyl ketone and toluene) oxidation. Additionally, catalysts were tested in particulate matter (PM) combustion. The characterization results indicated that Ce is in the form of Ce4+ and Ce3+, and Mn existed in the form of Mn4+ and Mn3+ on the surface of the Mn/AC sample and in the form of Mn4+ in the Ce/Mn/AC monolith. VOC oxidation results revealed that the Ce/Mn/AC sample shows an excellent performance compared with ceramic supported CeO2 (Ce/AC) and MnOx(Mn/AC) samples. The PM combustion was also higher on Ce/Mn/AC monoliths.The enhanced catalytic activity was mainly attributed to the Ce and Mn interaction which enhances the acidity, conductivity and the reducibility of theoxides.